Laju Eksploitasi Sumberdaya Ikan Layang (Decapterus macrosoma) yang didaratkan di Pangkalan Pendaratan Ikan (PPI) Kota Sorong-Papua Barat - Misbah Sururi; Mustasim Mustasim; Franklyn Hoek; Anasri Anasri (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2017)
The study related to the size and the exploitation rate of Shortfin scad are important in order to see the development condition of resource, especially on stock availibility for the management of its sustainability. This study was conducted in April - September 2013 at The Fish Landing Base (PPI) of Sorong, West Papua. This study aims to analyze the biology aspects of Shortfin scad based on itss length frequency, length-weight relationship, growth rate, mortality rate and exploitation rate of the catch.The primary data was acquired by the measurement of length and weight of Shortfin scad landed by purse seiner and from interview with the fishermen. The number Shortfin scad measured during reseach was 1.504 individuals which classified by the size of class interval, the data then analyzed to see the length-weight relationship and growth rate parameter analysis (L¥and K) by using the program of FAO-ICLARM stock of the assessment tools II (FiSAT II). The results showed that the frequency and normal distribution of total length, midlength is dominated by class interval of 16,0 - 16,5 cm. The correlation between weight and length of the individual is not significantly differ with the value of b = 3,57 (positive allometriks). The length (Loo) and weight asymptotic (Loo) are 21,83 mm and 105,4 grams respectively, this is allegedly estimated that the age of Shortfin scad is approximately of 40 months or 3.3 years. The result of exploitation rate acquired from the comparison between the mortality rate of catch and total mortality (E = F / Z) is 0,35. This indicating that the exploitation rate of Shortfin scad (Decapterus macrosoma) in purse seine fisheries at the time of research is still small due to smaller value compared to the optimal value when F = M or E = 0,5.